Transparência fiscal internacional e administração tributária em rede: o sistema regulatório e prático do intecâmbio de informações tributárias no Brasil e os direitos e garantias fundamentais dos contribuintes - Bastos, Frederico Silva (2014)
The phenomenon of globalization has enabled the internationalization of organizations, the free movement of capital and intensified global competition for new markets. While in the past fiscal policies were established aiming only to the solution of domestic problems, with globalization it is required that the tax authorities are prepared to act and plan your policies also globally. To cope with that, new forms of regulation and regulators emerge. Under this view, an effort towards signing international treaties, conventions, and agreements seems to be a feasible solution. In this sense, the experiences of cooperation and the models proposed by international organizations are relevant and Brazil should continue to be included in that scenario. However, these instruments can not be transplanted straightforwardly to the Brazilian legal system, it is necessary to adapt them to our reality. In the tax context, a valuable and viable tool in monitoring and combating aggressive tax planning and tax evasion has been the exchange of information between tax administrations. Assuming the problem of the absence of specific regulations, as well as the absence of uniform administrative procedure by the RFB we sought to map the regulatory system and the administrative practices for the international exchange of tax information in Brazil in order to better understand the procedure of Brazilian tax administration regarding international cooperation in tax matters. Regarding the Brazilian regulatory framework, it is found that there are constitutional principles and infra-constitutional norms that make international cooperation for the exchange of information with other countries possible, however, exists rights of Brazilian taxpayers that can not be avoided and that demand concern regarding the adequacy of the tools of international cooperation in tax matters concluded by Brazil. Regarding the practice framework, it was found that the RFB has infrastructure that enables the availability of reliable and timely information, access and authority to obtain information from taxpayers or third parties when necessary. From the analysis of the regulatory and practical framework for the international exchange of tax information in Brazil, it was pointed out that the efficiency of information exchange in the country can be mitigated by frictions between this method of international cooperation and fundamental rights and guarantees under the Brazilian Constitution in relation to privacy, intimacy, due process, nonretroactivity and the equality.